2005
DOI: 10.1016/j.biopsych.2005.04.034
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Correlates of Nonaffective Psychosis in the National Comorbidity Survey Replication (NCS-R)

Abstract: Background-To estimate the prevalence and correlates of clinician-diagnosed DSM-IV nonaffective psychosis (NAP) in a national household survey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
241
3
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 359 publications
(272 citation statements)
references
References 41 publications
15
241
3
5
Order By: Relevance
“…This interpretation dovetails with findings from several studies that describe disparities in access to and forms of mental health treatment by race [e.g., Sohler et al, 2004;Jarvis et al, 2014;Kuno and Rothbard, 2014]. An ascertainment bias of this kind could have a broad impact on psychosis research because many studies recruit from such sites, especially large cohort studies that utilize targeted recruitment methods to offset the low base rate of psychosis in the community [Kessler et al, 2005]. Clearly, the possibility of a systematic disparity in access to treatment affecting African Americans with psychosis requires further research.…”
Section: Discussionsupporting
confidence: 63%
“…This interpretation dovetails with findings from several studies that describe disparities in access to and forms of mental health treatment by race [e.g., Sohler et al, 2004;Jarvis et al, 2014;Kuno and Rothbard, 2014]. An ascertainment bias of this kind could have a broad impact on psychosis research because many studies recruit from such sites, especially large cohort studies that utilize targeted recruitment methods to offset the low base rate of psychosis in the community [Kessler et al, 2005]. Clearly, the possibility of a systematic disparity in access to treatment affecting African Americans with psychosis requires further research.…”
Section: Discussionsupporting
confidence: 63%
“…Similarly National Comorbidity Survey (NCS) (Kessler et al, 1994;Kendler et al, 1996) reveals 45% of comorbidity between substance abuse and schizophrenia while more recent National Comorbidity Survey Replication (NCS-R) (Kessler et al, 2005) reports 26.8% of lifetime comorbidity of non-affective psychosis with SUD. Furthermore, epidemiological investigations conducted outside United States support high prevalence of both substance abuse in psychotic disorders (Kavanagh et al, 2004;Addington and Addington, 2007) and SUD in schizophrenia (Fowler et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In the last two decades there were many epidemiologic studies, that provided a better understanding about the occurrence and development of mental disorders, some examples are: the ECA Study -Epidemiologic Catchment Area: A Survey of Mental Disorders, by the National Institute of Mental Health (1980)(1981)(1982)(1983)(1984)(1985) [2,3]; the NCS -National Co-morbidity Survey (1990Survey ( -1992 [4], and the NCS-R -National Comorbidity Survey Replication (2001)(2002)(2003) [5,6]. These studies provided knowledge of the direct and indirect consequences of mental disorders with personal, family and social impairment, as well as detailed information on the frequency and risk factors of these illnesses.…”
Section: Introductionmentioning
confidence: 99%
“…The statistics resultant from the two major epidemiologic studies conducted in the USA (the ECA and the NCS) [3,5,6], revealed that 22-23% of adult Americans (over 18 years old), had a mental disorder diagnosed by the Diagnostic and Statistical Manual of Mental Disorders (4th revision) (DSM-IV), in a one-year period [21,22]. The 2004 census showed a growth of these statistics, its results revealed that 26.2% of adult Americans [23], one in every four [6], had a mental disorder.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation